Human Resource Management Features of an Innovative Cluster - Doronina, Iuliia I.; Kulikova, Natalia N.; Razzhivin, Oleg A.; Kostyukhin, Yuri Y.; Silnov, Dmitry S.; Sadovnikova, Natalya A. (International Review of Management and Marketing, 2016)
Relevance of the study chosen subject is caused by that in modern time the productive solution of the questions connected with the personnel management, selection, training has a great value in the development and formation of the organizations, enterprises, and innovative associations. Now marked the change method, type, technology, transition phase, due to the acceleration of the social systems development, the emergence of new social relationships, relationships. Thus, it is considered to be the most essential phenomenon of the present stage of the society development of the ownership forms change with means of production, orientation of reforms with the market methods of managing and management, newest to the Russian Federation. In such circumstances, especially important is the organization and development question of the new social subject – the innovation cluster country, region, sector, which is assigned a significant role in developing and mastering the socio-economic area market. On the one hand, innovative cluster acts as a social group, goals and values that involve adaptation to the socio-economic situation, on the other – as a social system uniting groups, business organizations, impact on the environment by improving the socio-economic situation of the economic market. However, along with it there are social and administrative problems as contradictions between data on needs for productive practical actions for human resource management of a cluster and ignorance of implementation mechanisms of these actions. Keywords: personnel, management, innovations, cluster, enterprise, competitiveness JEL Classifications: M12, E24, M21